Leadership Strategy in Educational Institutions - Utami, Maharani Windu; Muiz, Rizqi Nurlaili; Zohriah, Anis; Bachtiar, Machdum (Mudir: Jurnal Manajemen Pendidikan, 2025)
Leadership in educational institutions has a strategic role in determining the success of an institution in achieving its vision and mission. Education leaders are not only responsible for administration and management, but also play a role in creating a conducive learning environment and encouraging innovation and improving the quality of education. This article discusses the concept of leadership in the context of educational institutions, including effective leadership styles, challenges faced, and strategies for improving leadership quality. With the right approach, leadership in educational institutions can contribute to improving the quality of learning, professional development of educators, and improving student performance. Therefore, it is important for education leaders to have managerial skills, effective communication, and the ability to adapt to changes in the world of education.